Teacher's Understanding of Elementary School Teacher Quality Components in Education Unit Accreditation Instruments - Riki Rahman Nurhakim; Wifa Fakhriyah Latifah; Nurul Firdaus; Yoga Sunandar (Jurnal al-Thullab, 2023)
The education process can run smoothly if it has a competent teacher quality. Schools must ensure the quality of teachers in order to produce quality teachers. This study aims to determine the understanding of educators in the Education Unit Accreditation Instrument (IASP) 2020 in order to improve the quality of education at SD/MI Serangpanjang, Subang, Indonesia by using the mechanism of the accreditation component. The method used is descriptive qualitative with data from interviews, distributing research questionnaires, and document studies. The results showed that the IASP 2020 could be understood well by teachers at SD/MI, Serangpanjang District, Subang Regency. Teachers at SD/MI, Serangpanjang Sub-district, Subang Regency can understand the statements in the 2020 Education Unit Accreditation Instrument. The conclusion is that the understanding of Islamic Religious Education and Teachers of Non-Islamic Religious Education regarding the quality components of elementary school teachers is well understood. The research is completed with the hope that it can be taken into consideration in improving the quality of teachers. Proses pendidikan dapat berjalan dengan mulus jika mempunyai mutu guru yang berkompeten. Sekolah harus melakukan proses penjaminan mutu guru setiap saat agar dapat menghasilkan guru yang berkualitas. Penelitian ini bertujuan untuk mengetahui serta mendeskripsikan pemahaman pendidik dalam Instrument Akreditasi Satuan Pendidikan (IASP) 2020 guna meningkatkan mutu pendidikan di SD/MI Serangpanjang, Subang, Indonesia dengan menggunakan mekanisme komponen-komponen akreditasi. Metode yang digunakan yaitu kualitatif deskriptif dengan data hasil wawancara, penyebaran angket peneltian, dan studi dokumen. Hasil penelitian menunjukkan bahwa IASP 2020 dapat di pahami dengan baik oleh guru di SD/MI Kecamatan Serangpanjang Kabupaten Subang. Hasil pemahaman pendidik di SD/MI Kecamatan Serangpanjang Kabupaten Subang dengan hasil akhir guru dapat memahami pernyataan-pernyataan dalam Instrument Akreditasi Satuan Pendidikan 2020. Oleh karena itu dapat dikatakan bahwa pemahaman guru Pendidikan Agama Islam dan Non Pendidikan Agama Islam mengenai komponen mutu guru tingkat SD sudah dipahami dengan baik. Penelitian ini diselesaikan dengan harapan dapat menjadi bahan pertimbangan dalam peningkatan kualitas guru.